2021
DOI: 10.3389/fimmu.2021.773146
|View full text |Cite
|
Sign up to set email alerts
|

Activation of T-bet, FOXP3, and EOMES in Target Organs From Piglets Infected With the Virulent PRRSV-1 Lena Strain

Abstract: Transcription factors (TFs) modulate genes involved in cell-type-specific proliferative and migratory properties, metabolic features, and effector functions. Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important pathogen agents in the porcine industry; however, TFs have been poorly studied during the course of this disease. Therefore, we aimed to evaluate the expressions of the TFs T-bet, GATA3, FOXP3, and Eomesodermin (EOMES) in target organs (the lung, tracheobronchial lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…In particular, virulent Lena strain induced a more severe and earlier onset of lung lesion from 6 dpi onwards as consequence of severe interstitial pneumonia, characterized by thickening of the alveolar septa ( Figures 1B , D ), together with extensive foci of suppurative bronchopneumonia composed of neutrophils, cell debris and mucus filling the bronchial, bronchiolar and alveolar lumen ( Figure 1E ). By contrast, no relevant differences between experimental groups were found in the gross and microscopic examination for tracheobronchial lymph node upon PRRSV-1 infection ( Figures 1F , H ), nevertheless, an increase in the number of tingible body macrophages and/or severe lymphoid depletion were observed in particular 3249- and Lena-infected animals ( Figure 1G ; Ruedas-Torres et al, 2021a ).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In particular, virulent Lena strain induced a more severe and earlier onset of lung lesion from 6 dpi onwards as consequence of severe interstitial pneumonia, characterized by thickening of the alveolar septa ( Figures 1B , D ), together with extensive foci of suppurative bronchopneumonia composed of neutrophils, cell debris and mucus filling the bronchial, bronchiolar and alveolar lumen ( Figure 1E ). By contrast, no relevant differences between experimental groups were found in the gross and microscopic examination for tracheobronchial lymph node upon PRRSV-1 infection ( Figures 1F , H ), nevertheless, an increase in the number of tingible body macrophages and/or severe lymphoid depletion were observed in particular 3249- and Lena-infected animals ( Figure 1G ; Ruedas-Torres et al, 2021a ).…”
Section: Resultsmentioning
confidence: 85%
“…Gross and histological findings for lung and tracheobronchial lymph node have been previously reported ( Rodríguez-Gómez et al, 2019 ; Ruedas-Torres et al, 2021a ). Macroscopic score of lungs is represented in Figure 1A (see Rodríguez-Gómez et al, 2019 for more details).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Another study showed that after infection with the Lena PRRSV strain, the expression of T-bet, Foxp3, and EOMES increased significantly, and at the same time, the expression level of IFN-γ also increased significantly. Importantly, the three significantly overexpressed transcription factors are closely related to the polarization of immune cells (Th1 cells, T cells, CD4+ cytotoxic T lymphocytes, and effector CD8+ T cells) (Ruedas-Torres et al, 2021 ).…”
Section: The Role Of Transcription Factors In Prrsv Infectionmentioning
confidence: 99%